Histone deacetylase inhibitor suberoylanilide hydroxamic acid reduces acute graft-versus-host disease and preserves graft-versus-leukemia effect - Reddy, Pavan (National Academy of Sciences, 2004)
Acute graft-versus-host disease (GVHD) and leukemic relapse are the two major obstacles to successful outcomes after allogeneic bone marrow transplantation (BMT), an effective therapy for hematological malignancies. Several studies have demonstrated that the dysregulation of proinflammatory cytokines and the loss of gastrointestinal tract integrity contribute to GVHD, whereas the donor cytotoxic responses are critical for graft-versus-leukemia (GVL) preservation. Suberoylanilide hydroxamic acid (SAHA) is currently in clinical trials as an antitumor agent; it inhibits the activity of histone deacetylases and at low doses exhibits antiinflammatory effects by reducing the production of proinflammatory cytokines. Using two well characterized mouse models of BMT, we have studied the effects of SAHA on GVHD severity and GVL activity. Administration of SAHA from day +3 to day +7 after BMT reduced serum levels of the proinflammatory cytokines and decreased intestinal histopathology, clinical severity, and mortality from acute GVHD compared with vehicle-treated animals. However, SAHA had no effect on donor T cell proliferative and cytotoxic responses to host antigens in vivo or in vitro. When mice received lethal doses of tumor cells at the time of BMT, administration of SAHA did not impair GVL activity and resulted in significantly improved leukemia-free survival by using two different tumor and donor/recipient combinations. These findings reveal a critical role for histone deacetylase inhibition in the proinflammatory events contributing to GVHD and suggest that this class of pharmacologic agents may provide a strategy to reduce GVHD while preserving cytotoxic T cell responses to host antigens and maintaining beneficial GVL effects.